Meal-Sensing Signaling Pathways in Functional Dyspepsia - Page, Amanda J.; Li, Hui (Frontiers in Systems Neuroscience, 2018)
The upper gastrointestinal tract plays an important role in sensing the arrival, amount and chemical composition of a meal. Ingestion of a meal triggers a number of sensory signals in the gastrointestinal tract. These include the response to mechanical stimulation (e.g. gastric distension), from the presence of food in the gut, and the interaction of various dietary nutrients with specific ‘taste’ receptors on specialised enteroendocrine cells in the small intestine culminating in the release of gut hormones. These signals are then transmitted to the brain where they contribute to food intake regulation by modulating appetite as well as feedback control of gastrointestinal functions (e.g. gut motility). There is evidence that the sensitivity to these food related stimuli is abnormally enhanced in functional dyspepsia leading to symptoms such nausea and bloating. In addition, these gut-brain signals can modulate the signalling pathways involved in visceral pain. This review will discuss the role of gut-brain signals in appetite regulation and the role dysregulation of this system play in functional dyspepsia.